What are the risks and benefits of doing mammograms in women ages 40–49 at average risk of breast cancer?. Issue 7 (July 2015) - Vermani, Prathiba; Bhattacharyya, Adity
Abstract : Evidence‐Based Answer : Mammographic screening for women 40–49 years of age at average risk of breast cancer yields a 7%‐23% absolute decrease in breast cancer mortality compared with a 22% reduction in women older than 50, but its use should be balanced with the increased risk of false‐positive results (20%‐61%) and overdiagnosis (19% over 10 years) associated with early screening (SOR: A, based on systematic reviews of RCTs with consistent findings).